Sodium chloride reduces the viability of eggs, larvae, and pupae of Spodoptera frugiperda, as well as delays its development (Research, Society and Development, 2022)
The control of fall armyworm (Spodoptera frugiperda) populations involves the application of pesticides that cause several unwanted effects to humans and other animals, as well as to environment. Sodium chloride (NaCl) has been used in agriculture to potentiate the toxicity of pesticides. Here, the effects of NaCl on the viability of eggs, larvae, and pupae, as well as on development of S. frugiperda were evaluated. The treatment with 0.15 M NaCl caused a 35% reduction of egg hatching and the ingestion of artificial diet containing the salt caused mortality of caterpillars, pre-pupae, and pupae, as well as delayed the development of the insects. The larval, pre-pupa and pupa stages were elongated by about 2, 1 and 0.8 days, respectively. Additionally, significant reduction in pupae body weight was recorded in groups treated with NaCl at 0.62 mg/g and 3.12 mg/g. Despite these effects, NaCl ingestion did not affect the viability of adults and their reproductive performance. Food deterrent assay revealed that the salt acted as a phagostimulant agent. In conclusion, NaCl reduces the hatching of S. frugiperda eggs and damage the survival of carterpillars and pupae, as well interferes with insect development.